Estate Planning for the Man with a Business - Bertram W. Tremayne (Washington University Law Quarterly, 1955)
One of the most challenging situations in the estate planning field is presented by an individual who owns all or a substantial part of a business, be it a corporation, partnership, or sole proprietorship. The problem is how to transfer the business interest to the objects of the owner's bounty with as little reduction in capital and loss of income as possible. Under our present tax structure, without careful estate planning, or perhaps even with it, the death of a founder or chief executive of a closely held business is apt to destroy or greatly reduce its value. While this is especially true of professional or other personal service enterprises, it is also true of businesses such as manufacturing concerns, where capital is a major factor and where, accordingly, it might be expected that the value of the business would be capable of being transferred over to the heirs of the deceased owner. The heavy bite of death taxes, federal and state, and the other “costs of dying” represent a major threat to a family fortune founded on a closely held business.
Keywords: Estate planning